A SCHEDULING ON IMPLEMENTATION OF ISDB PROJECT JEMBER UNIVERSITY WITH PRECEDENCE DIAGRAM METHOD - Icha Tatrisya Derka; Hernu Suyoso; Anik Ratnaningsih (Jurnal Rekayasa Sipil dan Lingkungan, 2019)
Scheduling is important, because of the time limit, so the implementation of project activities must be planned and timely. The Integrated Laboratory for Natural Science and Food Technology building is one of the development projects of the IsDB (Islamic Development Bank), in the Jember University. In this study, the schedule will be carried out using the PDM method (Precedence Diagram Method), assisted by the Microsoft Project. The PDM is a working network with a clear dependency relationship and can be used on projects that have overlapping activities between tasks to another, PDM can show critical trajectory. Secondary data needed in the form of soft-drawings, BoQ (Bill of Quantity), City of Jember AHS 2018 and S curve. There are 30 jobs included in the critical track including 14 jobs in construction work, 11 jobs in architectural work and 5 jobs in outside work. The results of the study indicate that the duration of the construction Building is 242 days, or 8 months 16 days. Penjadwalan merupakan hal yang penting, karena adanya batasan waktu, maka pelaksanaan kegiatan proyek harus tepat rencana dan tepat waktu. Gedung Integrated Laboratory for Natural Science and Food Technology merupakan salah satu pembangunan proyek IsDB (Islamic Development Bank), yang ada di lingkungan Universitas Jember. Pada penelitian ini, akan dilakukan penjadwalan menggunakan metode PDM (Precedence Diagram Method) dibantu dengan Microsoft Project. PDM merupakan jaringan kerja dengan hubungan ketergantungan yang jelas dan dapat digunakan pada proyek yang mempunyai kegiatan tumpang tindih antar satu pekerjaan ke pekerjaan lainnya, serta dapat menunjukkan lintasan kritis. Data yang dibutuhkan berupa data sekunder yaitu gambar rencana, BoQ, AHS Kota Jember 2018 dan kurva S. Terdapat 30 pekerjaan yang termasuk dalam lintasan kritis meliputi 14 pekerjaan di pekerjaan strukur, 11 pekerjaan di pekerjaan arsitektur serta 5 pekerjaan di pekerjaan luar bangunan. Hasil penelitian menunjukkan bahwa jangka waktu pelaksanaan pembangunan Gedung Integrated Laboratory for Natural Science and Food Technology adalah selama 242 hari, atau 8 bulan lebih 16 hari.